2023
DOI: 10.1002/mrd.23683
|View full text |Cite
|
Sign up to set email alerts
|

The vascular endothelial growth factor (VEGF) system as a key regulator of ovarian follicle angiogenesis and growth

Abstract: The vascular endothelial growth factor‐A (VEGFA) system is a complex set of proteins, with multiple isoforms and receptors, including both angiogenic (VEGFxxx, VEGFR2) and antiangiogenic members (VEGFxxxb, VEGFR1 and soluble forms of VEGFR). The members of the VEGF system affect the proliferation, survival, and migration of endothelial and nonendothelial cells and are involved in the regulation of follicular angiogenesis and development. The production of VEGF by secondary follicles stimulates preantral follic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 167 publications
0
9
0
Order By: Relevance
“…Furthermore, the physiological role of hCG in increasing VEGF expression in granulosa cells during the luteal phase has been well-documented (Fang et al 2019 ; Wang et al 2021 ). The pivotal function of VEGFA in promoting angiogenesis and increasing vascular permeability to maintain blood supply to the corpus luteum has highlighted its significance in follicular growth and luteum function (Guzmán et al 2023 ). It has been also reported that the excessive secretion of VEGF by hormone-stimulated follicles can significantly increase VEGF levels beyond the physiological threshold, thus triggering elevated vascular permeability and the subsequent onset of OHSS (Li et al 2019 ; Luo et al 2021 ; Mills and Dahan 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the physiological role of hCG in increasing VEGF expression in granulosa cells during the luteal phase has been well-documented (Fang et al 2019 ; Wang et al 2021 ). The pivotal function of VEGFA in promoting angiogenesis and increasing vascular permeability to maintain blood supply to the corpus luteum has highlighted its significance in follicular growth and luteum function (Guzmán et al 2023 ). It has been also reported that the excessive secretion of VEGF by hormone-stimulated follicles can significantly increase VEGF levels beyond the physiological threshold, thus triggering elevated vascular permeability and the subsequent onset of OHSS (Li et al 2019 ; Luo et al 2021 ; Mills and Dahan 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, TNF-α has been shown to activate the NF-κB and PI3K/Akt signaling pathways, synergistically promoting the RANKL-induced formation of osteoclasts (Zha et al, 2018). VEGFA, a pivotal growth factor implicated in angiogenesis, exerts proproliferative and antiapoptotic effects on endothelial cells (Guzmán et al, 2023). Intriguingly, research conducted by Brissova et al (2014) demonstrates that exposure to doxycycline triggers VEGFA production in mouse islets, consequently reducing the number of β-cells as VEGFA levels surge.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF is a part of the VEGF / platelet-derived growth factors (PDGF) gene family, also known as the cystine junction superfamily of growth factors [21]. It was initially found in a variety of cultured tumor cell lines, which can directly act on vascular endothelial cells, promote the proliferation of vascular endothelial cells and improve vascular permeability [22].…”
Section: Comparison Of Genotype and Allele Frequencies Of Vegf Gene R...mentioning
confidence: 99%